Action of Language Teachers of Daarut Tauhid Elementary School during the Pandemic COVID-19 - Magribi, Bagja Dani; Hartati, Tatat; Agustin, Mubiar (International Conference on Elementary Education, 2021)
Learning during the pandemic period requires educators to know technology and master pedagogy skills well. Good teacher speaking speech acts are a form of skill that will have an impact on the character of students, especially at the elementary school level. This study aims to describe the speech acts used by elementary school teachers in learning during the pandemic. The method used is descriptive analysis method using a qualitative approach. The data source used was the speech acts of elementary school teachers. The technique used is the technique of recording, listening, and taking notes. Data analysis techniques consist of (1) data collection (2) data reduction (3) data presentation (4) verification or drawing conclusions. The results of this study are expected to describe the forms of directive, representative, expressive, commissive, declarative speech acts, and direct and indirect speech acts to elementary school teachers in learning during the pandemic.